(untitled) (The Conference Hub, 2025)
Magnesium-rich foods play a fundamental role in maintaining optimal health and preventing chronic diseases. As a vital macronutrient, magnesium is involved in over 300 enzymatic reactions responsible for energy production, muscle function, and nerve transmission. Adequate intake of magnesium-rich foods — such as leafy green vegetables, nuts, seeds, legumes, whole grains, and mineral-rich water — helps regulate cardiovascular function, strengthen bones, and improve metabolic balance. Numerous studies have demonstrated that dietary magnesium contributes to the prevention of hypertension, diabetes, osteoporosis, and neurological disorders. Despite its importance, magnesium deficiency remains prevalent globally due to the widespread consumption of processed foods low in minerals. Therefore, promoting the inclusion of magnesium-rich foods in daily diets is crucial for maintaining physiological stability, enhancing immunity, and reducing the risk of chronic diseases.